Perancangan Interior Fasilitas Musik Klasik di Surabaya - Giovanna Michelle Natasha; Hedy Constancia Indrani; Poppy Firtatwentyna Nilasari (Intra, 2019)
Classical music is one type of music that has benefits for human life. However, people do not have any interest in learning classical music because the thought of its difficulties to understood and the facilities provided are limited only for those who involved in certain musical institutions. Therefore, the design provides an opportunity for lay people and classical music lovers to be able to explore classical music even further. The classical music facilities are for public. Simple, soft, and expressive formations characteristics are arranged in a way that provides a certain atmosphere to supports both lay people and music lovers. Facilities that are provided including the Lobby area, Gallery Area, Library Area, Store Area, Studio Area, Recital Hall, and Office Room - Meeting Room. With the concept of